The Extraction and Partial Purification of Wedelolactone from Local Eclipta alba Plant - Shanshol, Zainab; Alaubydi, Mouruj; Sadik, Ali (Iraqi Journal of Science, 2024)
Abstract:Eclipta alba is a weed growing in damp, moist puddles distributed in the tropical and subtropical regions, so the most weight of the plant is water, which reached in to 90%. The extraction method by using different solvents (Methanol, Ethanol, Hexane and Aqueous) showed, the best yield with methanol reached to 76%, and the yield decreased with ethanol and hexane reached 55% and 53% respectively, while the minimum yield observed with aqueous hot and cold extraction reached 11% and 5% respectively. The phytochemical compound characterization showed the compounds (Coumarines , Flavones ,Volatile Oil ,Tannins , Saponines , Glycosides ,Carbohydrates ,Alkaloids , Resins) with different percentage. The thin layer chromatography detection for wedelolactone showed appositive result according to the appearance of purple to a violet color under UV .light, and the value of RF was reached to 0.56 cm .The purification method showed one main peak between the fractions (7-22). The melting point for wedelolactone was 328. The HPLC result showed compatibility between both sample and standard wedelolactone in shape, and the retention time for the sample was 2.157 which is closely related with the standard one 2.163 , and the concentration of the wedelolactone was 99.27